The international responsibility of the World Health Organization (WHO) in times of pandemic - Franciskovic Ingunza, Millitza (2020)
The World Health Organization has a high responsibility to effectively manage the virus that has caused the pandemic that is currently ravaging the planet. It is an organism whose cardinal function is to protect the health of the entire humanity. However, it can be seen that the behavior of the WHO in the face of this tragedy has been that of acting with tremendous slowness. It has lacked the necessary reflexes in order to resume the functions that were entrusted to it in its constitutive document. In this article, we consider the existence of international responsibility on the part of the WHO as the Director-General. Any international organization must account for its conduct in such dire circumstances.